The Impact of Technology Use in Teaching and Understanding Religious Values on Students' Moral Development in Islamic Schools in Indonesia - Muhammad Rusdi; Rika Riwayatiningsih; Herman Taufik; Andi Fitriani Djollong (Eastasouth Institute, 2023)
This study investigates the impact of technology in teaching and the understanding of religious values on the moral development of students in Islamic schools in Indonesia. A quantitative analysis using Structural Equation Modelling with Partial Least Squares (SEM-PLS) was employed to examine the relationships among these key variables. The study's questionnaire demonstrated strong validity and reliability. Discriminant validity confirmed the distinctiveness of the constructs. Hypothesis tests revealed significant positive relationships between Religious Values and Students' Moral Development and between Technology Use in Teaching and Students' Moral Development. These results underscore the critical role of both religious values and technology-enhanced teaching methods in shaping the moral character of students. The findings provide valuable insights for educators and policymakers in Islamic schools, emphasizing the potential of technology in religious education without compromising moral development.